Extração, caracterização e toxidade da pectina do noni (Morinda citrifolia L.) - Santos, Denilton Garcia (2015)
Noni (Morinda citrifolia L.) is a plant that has aroused the interest of the scientific community. However there are few scientific papers on the pectin extracted from this fruit. The extraction was conducted at three pH’s tracks (3, 7 and 10), within a time interval and set temperature. Three different extracting agents were used. The pectin extracted at pH 3 (PDN-a) was subjected to the process of sulfation and confirmed by elemental analysis. All samples from pectin extraction processes and citrus pectin commercial use (Vetec®) were characterized by FT - IR, it was possible to determine the degree of esterification (30%) which was confirmed with the results obtained By potentiometric titration and 1H NMR. Through the GPC and viscosity analyzes it was possible to determine respectively the molecular weights of the pectin samples (3.8 x105 6.8 x105 g / mol). The NMR analysis of 1H were important in determination of the five signals corresponding to hydrogens of the galacturonic acid chain. Now the thermal analysis, TGA and DSC, observed the range of stability of pectins and compare in relation to citrus pectin commercial use. In AFM analysis it was possible to observe the molecular level how the structure of pectin was affected (fragmented) by extraction and sulfation process. In the analyzes Zeta potential was confirmed the anionic character of the pectin chain (-32.2 mV and -42.1 mV) to the pectin extracted at acid pH and their sulfated sample. It was determined Surface Tension and Critical Micelle Concentration (CMC) for the pectin sample (pH 3). The rheological study and some physicochemical properties such as moisture content, Determination of lipids, Determination of protein and soluble fiber determination were also performed. The PDN-a sample -the one with a better yield (19%) and its polymer chain was little affected by the extraction process, was subjected to in vivo toxicological tests (mice), which had undertaken an acute oral toxicity test, Determination of haematological and biochemical parameters and check the wet relative weight of organs, where its toxicity has been dropped. PDN-s (sulfated pectin) was used for in vitro cytotoxicity testing (human blood) and verification of the enzyme lactate dehydrogenase activity, where no significant differences compared to controls used.